Prawoznawstwo — polityczność nauki czy nauka polityczności? - Zajadło, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Considering the main subject of XXII Congress of the Chairs of Theory and Philosophy of Law the author tries to answer the following question: “Jurisprudence — the political of science or science of the political?”. His answer is clear — we need the latter and not the former. In the article the concepts of „politics”, „political” and „politization” are treated synonymously. The problem is presented on the background of Carl Schmitt’s political philosophy. In the author’s opinion after 1933 Schmitt has balanced between these two attitudes (the political of science or science of the political) because of his methodology (political theology) on the one hand, and of his personal choice (support for Nazi regime) on the other. In the last part of the article are formulated some conclusions — learned from Schmitt’s lesson and concerning the constitutional crisis in Poland
Keywords: prawoznawstwo; polityka; polityczność; prawo; teoria prawa; Niemcy